Ripening of salted anchovy (Engraulis anchoita): Development of lipid oxidation, colour and other sensorial characteristics - Czerner, Marina (2010)
BACKGROUND: Changes in lipids are in general associated with quality deterioration, though earlier studies in anchovy indicate that the volatile compounds of importance to the characteristic flavour could be generated by lipid oxidation. The aim of the present paper was to study the changes in the fatty acid composition and the lipid oxidation of Engraulis anchoita during ripening and their relationship with the development of the typical sensorial characteristics. RESULTS: As a result of ripening, polyunsaturated fatty acids decrease from 4.27 to 2.42 and 2.00 g kg−1 fatty acids in gutted fish and fillet, respectively. The most affected class of fatty acids was the n-3 fatty acids, especially docosahexaenoic acid. Moreover, saturated fatty acids were the most stable to the process. 2-Thiobarbituric acid reactive substances (TBARS) increased throughout ripening, and the use of fillets instead of gutted fish reduced this value. The a* value was the parameter most modified, showing a marked increase which correlates with the acquisition of a uniform pink colour. Sensory analysis did not show development of off-odour or undesirable changes in colour during ripening. CONCLUSION: As a result of ripening, the fatty acid profile was modified and an increment of TBARS was observed. However, these changes did not lead to deterioration in the quality of the product.